Stability and growth in a global economy - Visco, Ignazio (PSL Quarterly Review, 2019)
The hopes that dawned with the end of the Cold War of improving everyone’s well-being through globalisation and technological progress have been partly disappointed. They have been replaced by uncertainty about the effects of these profound changes on the distribution of wealth, the availability of work, the possibility of growth continuing at the same pace as in the last few decades, the impact on the environment, the consequences of demographic trends, and the balance of power between countries, between companies, and between companies and consumers. The need to govern these changes is now clear and greater attention must be paid to those who have difficulty adapting, not only in advanced countries, where automation and global competition are displacing many workers employed in routine jobs, but also in emerging and developing countries, where the prospects of further poverty reduction are diminishing. These are crucial challenges for the world economy. JEL codes: F6, O33, Q54, J11